Effect of cataract surgery on intraocular pressure in supine and lateral decubitus body postures - Park, Ji-Hye; Yoo, Chungkwon; Song, Jong-Suk; Lin, Shan; Kim, Yong (Indian journal of ophthalmology, 2016)
Purpose: To investigate the effect of phacoemulsification on intraocular pressure (IOP) in different recumbent body postures including supine and lateral decubitus (LD) positions. Materials and Methods: This prospective, observational study included patients who had no glaucoma and who had planned to undergo phacoemulsification and intraocular lens implantation in one eye. Before and 1 month after cataract surgery, IOP was measured in both eyes using the Tono-Pen AVIA. We measured IOP in the sitting, supine, and LD (with the operated eye placed on the lower side) positions. IOP was measured 10 min after assuming each position in a randomized sequence. The Wilcoxon signed-rank test was used to compare the IOP changes before and 1 month after phacoemulsification in all postures. Results: Twenty-nine patients participated in this study. Postoperative IOP was lower than the preoperative IOP when measured by Goldmann applanation tonometry in the sitting position (13.8 ± 1.9 mmHg vs. 12.6 ± 2.1 mmHg, P = 0.007). The postoperative IOP was lower than the preoperative IOP for the supine and LD positions. The average IOP reduction of the operated eye was 0.6 mmHg, 1.7 mmHg, and 3.0 mmHg in the sitting, supine, and LD positions, respectively (sitting vs. supine, P = 0.048; sitting vs. LD, P = 0.001; supine vs. LD, P = 0.028). In the nonoperated eye, IOP did not change significantly after surgery (all P > 0.05). Conclusions: Cataract surgery lowered IOP in the sitting position as well as in the supine and LD positions. Such postoperative IOP reductions were greater in the recumbent positions than in the sitting position.